Micropulse transscleral cyclophotocoagulation for the treatment of glaucoma - N. S. Khodzhaev; A. V. Sidorova; A. V. Starostina; M. A. Eliseeva (Российский офтальмологический журнал, 2020)
Because of the unpredictable hypotensive effect and serious complications during continuous-wave cyclophotocoagulation (CW-CPC), the use of this method in the treatment of glaucoma is limited. Therefore, a new technique was developed, known as micropulse trans-scleral cyclophotocoagulation (MP-CPC). During MP-CPC, a series of short bursts of laser pulses deliver energy to the ciliary body at the near-infrared wavelength of 810 nm, which is strongly absorbed by melanin. As shown by experimental studies, there are several acting mechanisms which reduce IOP decrease during MP-CPC. In clinical studies, patients with different forms and stages of glaucoma received laser energy of similar parameters during MP-CPC. It may be concluded that MP-CPC is a safe and effective alternative to traditional CW-CPC. However if laser irradiation directed to the ciliary body during MP-CPC gets longer, the incidence of complications increases. The variation of glaucoma forms in patients who underwent MP-CPC and a relatively small number of cases involved in the studies prevent us from making an unambiguous recommendation of this technique at the moment. An extensive research of the technique is required.